The Effect of the Work Environment on Job Satisfaction through Burnout - Indra Setiawan; Saur Panjaitan (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
The industrial sector is increasingly competitive, resulting in companies needing competent Human Resources (HR). The company must consider all HR needs to satisfy employees at work. Some things that need to be considered by the company are the company's work environment and the level of employee burnout. The aims of this study were 1) to determine the effect of the work environment on employee job satisfaction, 2) to determine the effect of burnout on employee job satisfaction, and 3) to determine the effect of the work environment on burnout and 4) to determine the effect of the work environment on job satisfaction through burnout. The population in this study is all manufacturing employees in Indonesia. Sampling was carried out using a non-probability technique, namely convenience sampling. Primary data was obtained by distributing closed-question questionnaires using a Likert scale. The analytical method used is Structural Equation Modeling (SEM) with the Partial Least Square (PLS) approach. The results showed that LK had an effect on KK and burnout. Burnout significantly affects KK, and LK affects KK through burnout.